Pengaruh Motivasi Kerja, Pelatihan, dan Efikasi Diri Terhadap Kinerja Barista Di Coffe Shop Banyumas - Muhamad Rizki Harmawan; Hengky Widhiandono; Akhmad Darmawan; Totok Haryanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The purpose of this study is to analyze the effect of training and self-efficacy on the performance of baristas in coffee shops in Banyumas. The study population consists of all 114 baristas working in various coffee shops in the area. The research instrument used was a questionnaire, and the sampling technique applied was a census method, meaning that the entire population served as respondents. The collected data were analyzed using Multiple Regression Analysis, t-tests, and F-tests with the assistance of SPSS Version 25. The results of the study indicate that training and self-efficacy have a positive and significant effect on barista performance, suggesting that baristas’ confidence in their ability to carry out job tasks plays an important role in improving their performance. However, work motivation was not found to have a positive and significant effect on barista performance, indicating that work motivation is not a key determining factor in performance improvement within the context of this study. Simultaneously, training, self-efficacy, and work motivation were shown to have a significant effect on barista performance. The adjusted R² value of 67.6% indicates that these variables explain 67.6% of the variation in barista performance, while the remaining 32.4% is influenced by other factors not examined in this study.